A clayey water-proof rock layer similar material and preparation method thereof
By polymerizing graphene and polyvinyl alcohol with high-purity mineral component materials in similar materials of clayey water-proof rock formations, graphene/polyvinyl alcohol/mineral polymers are generated, which solves the stress-strain problem of traditional similar materials. In order to solve the problem of insufficient similarity with natural rock mass in terms of water-rock interaction characteristics and other aspects, a new clayey water-isolating rock layer similar material with high similarity has been realized.
Patent Information
- Application Number
- CN202310072966.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-02
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2043-02-02
AI Technical Summary
When developing clay water-sparking rock formation similar materials and preparation methods, the existing technology lacks considerations for the intrinsic microstructure characteristics and mineral components of rocks, resulting in the traditional similar materials in stress-strain, water-rock action characteristics, etc. Insufficient similarity to natural rock mass.
The graphene nano -material is used as the strength regulating material, and the polyvinyl organic high molecular compound is used as the permeability regulatory material and glue material, and combined with high -purity mineral component materials to generate graphene/polyethylene/mineral polymer by polymerization reaction. Make sure that similar materials are similar to natural clay segregated rock body mineral composition.
Realizing the external strength, permeability, stress-strain, and water-rocks of the rock's external intensity, permeability, stress-strain, and water-rocks. , Significantly improved similarity.
Smart Images

Figure CN116161897B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a clayey water-proof rock layer similar material and a preparation method thereof, and is particularly suitable for similar preparation of clayey water-proof rock layers in physical simulation experiments such as geotechnical engineering and underground mining. Background Art
[0002] Clay impermeable rock strata are a kind of natural rock mass commonly found in strata. They are generally characterized by low strength and low permeability, and play an important role in achieving in-situ protection of water resources in the upper (or lower) aquifer. At the same time, clay impermeable rock strata are rich in clay minerals such as kaolinite, montmorillonite, and illite. When water-rock interaction occurs in rocks, the clay minerals expand and become muddy when exposed to water, which can make some rock cracks heal by themselves, making the clay impermeable rock strata have a certain ability to self-heal and block water. Especially for underground mining, clay impermeable rock strata are of great significance to the protection of water resources and the stability of the ecological environment in mining areas. The study of the stability of clay impermeable rock strata based on physical similarity simulation has always been one of the important issues that experts and scholars in the field have paid attention to. Its premise is the research and development of similar materials and preparation methods of clay impermeable rock strata.
[0003] At present, many experts and scholars have conducted extensive research on the proportion of similar materials for water-blocking layers. For example, patent CN115159942A uses river sand, bentonite, barite powder, iron powder, lime and gypsum to study the mudstone similar materials and preparation methods of tunnel surrounding rocks, and adjusts the strength, deformation modulus, internal friction angle and other parameters of mudstone similar materials by changing the different proportions of each material component; patent CN107098655A discloses a fluid-solid coupling similar material with polyurethane as a binder, and adjusts the strength, permeability coefficient and internal friction angle of similar materials by adjusting the different proportions of sand, calcium carbonate, polyurethane, cement, silicone oil and mixing water; patent CN112051389A proposes the use of coal powder, bentonite, clay, quartz sand, cement and water to reshape coal-bearing mudstone samples, simulating the similarity of strength, water absorption characteristics and expansion deformation characteristics of coal-bearing mudstone samples. Patent CN112028555A uses calcite, river sand and talcum powder as aggregates, cement, silicone rubber and glycerin as binders, acetic acid as a regulator, and water as an additive to prepare solid-liquid coupling similar materials, which expands the permeability coefficient of similar materials; Patent CN114105599A uses coal powder, water glass, polycarboxylic acid high-efficiency PC water reducer, silicon phosphate, gelatin and water as raw materials to prepare low-strength high-impact coal similar materials, and achieves similar simulation of the dynamic destruction characteristics of strong impact-prone coal. The above research provides reference for the research on similar materials of clayey impermeable rock formations and their preparation methods of the present invention, but there are still the following deficiencies:
[0004] (1) The invention is insufficient in terms of similar materials and preparation methods for clayey impermeable rock formations, and there is a lack of special similar materials and preparation methods that can be selected and used when conducting physical similarity simulations of clayey impermeable rock formations;
[0005] (2) The intrinsic microstructural characteristics of rocks (such as particle size, pore structure, etc.) and mineral components directly affect their external physical and mechanical properties. Previous studies did not consider similar materials such as rock external strength, permeability, and stress-strain characteristics from the perspective of the intrinsic microstructural characteristics and mineral components of rocks, resulting in a significant lack of similarity between traditional similar materials and natural rock masses in terms of stress-strain, water-rock interaction characteristics, etc.;
[0006] (3) The addition of binders such as cement and gypsum to traditional similar materials will change the mineral composition of the similar materials, making it difficult to achieve similarity in composition between the similar materials and natural rock masses.
[0007] Therefore, it is urgent to develop new clayey impermeable rock layer similar materials and their preparation methods based on the similarity of intrinsic mineral particle size and mineral composition to achieve similar external strength, permeability, stress-strain and water-rock interaction characteristics of rocks. Summary of the invention
[0008] The purpose of the present invention is to propose a clayey water-repellent rock formation similar material and a preparation method thereof, which is a new type of clayey water-repellent rock formation similar material and a preparation method thereof, which achieves similar external strength, permeability, stress-strain and water-rock interaction characteristics of the rock based on the similarity of intrinsic mineral particle size and mineral composition.
[0009] The clayey water-blocking rock formation similar material described in the present invention comprises a mineral component material, a strength regulating material, a permeability regulating and cementing material and water. The mineral component material comprises 10 to 90 parts of quartz sand, 5 to 70 parts of kaolinite powder, 5 to 50 parts of montmorillonite powder, 0.1 to 30 parts of illite powder, 0.1 to 30 parts of plagioclase powder, 0.1 to 20 parts of potassium feldspar powder and 0.1 to 20 parts of dolomite powder. The strength regulating material is 0.01 to 0.05 parts of graphene, the permeability regulating and cementing material is 5 to 15 parts of polyvinyl alcohol, and the water is deionized and accounts for 15 to 25% of the total material weight. The above components are all measured by mass.
[0010] Furthermore, the polyvinyl alcohol in the similar material undergoes polymerization reaction with the graphene and the mineral component material to generate a graphene / polyvinyl alcohol / mineral polymer.
[0011] Furthermore, the sum of the mass fractions of each component in the mineral component material is 100 parts, and the content fraction of each component is determined according to the actual content ratio of each component in the natural clayey impermeable rock mass.
[0012] Furthermore, the mass fractions of the graphene and polyvinyl alcohol are determined according to the triaxial compressive strength and permeability coefficient of the natural rock mass of the clayey impermeable rock layer, respectively. The detailed determination scheme is shown in the following table:
[0013]
[0014]
[0015] Furthermore, the mineral component material is a high-purity mineral material, and the purity of each component is ≥98%;
[0016] The quartz sand particle size is 100-2000 mesh, and the particle size is selected according to the actual particle size of the clayey water-proof natural rock mass;
[0017] The kaolinite powder is calcined kaolinite powder with a particle size of 2500-3000 mesh;
[0018] The montmorillonite powder is natural montmorillonite powder, and the particle size is 2000-3000 mesh;
[0019] The illite powder is natural illite powder with a particle size of 2500-3000 mesh;
[0020] The plagioclase powder is ultrafine plagioclase powder with a particle size of 2000-3000 mesh;
[0021] The potassium feldspar powder is natural potassium feldspar powder, and the particle size is 2000-3000 mesh;
[0022] The dolomite powder is natural dolomite powder, and the particle size is 2500-3000 mesh.
[0023] Furthermore, the graphene is powdered high-purity single-layer graphene with a particle size of 3-9nm.
[0024] Furthermore, the polyvinyl alcohol is PVA2488 cold water fast-soluble powdered polyvinyl alcohol with a viscosity of 55 to 68 mPa·s.
[0025] Furthermore, the similar material is suitable for physical similarity simulation experiments with a geometric similarity ratio of 1:100, a stress similarity ratio of 1:167, a time similarity ratio of 1:10, and a permeability coefficient similarity ratio of 1:10.
[0026] The method for preparing a similar material of a clayey water-proof rock layer described in the present invention comprises the following steps:
[0027] S1: Obtain natural rock samples of clayey impermeable rock strata through geological drilling; where: the diameter of the rock sample is ≥100mm, and the height of the rock sample is ≥120mm;
[0028] S2: Perform triaxial compressive strength and permeability test on the natural rock sample of the clayey impermeable rock layer obtained in step S1 to determine the triaxial compressive strength and permeability of the impermeable rock sample;
[0029] S3: Obtain a natural rock sample of a clayey impermeable rock layer according to step S1, and determine the particle size, type and content of each mineral component of the impermeable rock sample;
[0030] S4: according to the particle size of the water-blocking rock sample, the triaxial compressive strength, the permeability coefficient, the type and content of each mineral component obtained in steps S2 and S3, the particle size of the quartz sand particles is determined, and the mass fractions of quartz sand, kaolinite powder, montmorillonite powder, illite powder, plagioclase powder, potassium feldspar powder, dolomite powder, graphene and polyvinyl alcohol are weighed, and the above materials are uniformly stirred by a dry powder mixer to obtain a dry material mixture;
[0031] S5: According to the mass fraction of the dry material mixture obtained in step S4, deionized water of 15-25% of the mass fraction of the dry material mixture is weighed, added to the mixed dry material obtained in step S4, and quickly stirred to obtain the similar material to be prepared.
[0032] Furthermore, in step S3, the natural rock sample of the clayey impermeable rock layer obtained in step S1 is subjected to SEM scanning and XRD phase analysis to finally determine the particle size of the impermeable rock sample and the type and content of each mineral component.
[0033] The advantages of the present invention compared with the prior art are:
[0034] (1) Based on the similarity of the intrinsic particle size and mineral composition of rocks, a new type of clayey impermeable rock layer similar material with similar rock external strength, permeability, stress-strain and water-rock interaction characteristics was developed. The physical and mechanical properties of the similar material are more similar to those of natural rock mass. The strength of the mudstone simulated by the similar material is 12.38 MPa, and the relative error with the real mudstone strength is only 4.4%. The permeability coefficient is 7.81×10 -6 m / d, and the relative error with the true mudstone permeability is 5.6%;
[0035] (2) Using graphene nanomaterials as strength regulating materials and polyvinyl alcohol organic polymer compounds as permeability regulating materials and cementing materials will not change the type and content of mineral components of similar materials, and can ensure that the mineral composition of similar materials is similar to that of natural clayey impermeable rock mass;
[0036] (3) Polymers formed by polyvinyl alcohol, graphene and mineral component materials are rich in similar materials, with good overall cementation and dense structure, and the microstructure characteristics are similar to those of actual clayey impermeable rock. Polyvinyl alcohol organic polymer compounds have an irregular linear structure composed of many chain links, which can undergo polymerization reaction with graphene and mineral component materials to generate graphene / polyvinyl alcohol / mineral polymers, making the overall cementation of similar materials better, and the permeability and microstructure characteristics are more similar to those of actual clayey impermeable rock layers. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 This is the triaxial compression stress-strain curve of a real clayey impermeable cement rock, which has low strength, strain softening and obvious plastic deformation characteristics;
[0038] Figure 2 This is an electron microscope scanning picture of a real clayey rock with a dense structure and low porosity.
[0039] Figure 3 This is the X-ray diffraction spectrum of a real clayey silt rock, which is rich in clay minerals such as montmorillonite, illite, and kaolinite.
[0040] Figure 4 The triaxial compression stress-strain curve of the clayey barrier cement rock similar material prepared according to the present invention, the strength, strain softening and plastic deformation characteristics are similar to those of the actual clayey barrier cement rock;
[0041] Figure 5 This is an electron microscope scanning picture of a clayey barrier cement rock similar material prepared according to the present invention, which is rich in polymer, has good overall cementation, and a dense structure, and is similar to the microstructure characteristics of actual clayey barrier cement rock;
[0042] Figure 6 A schematic diagram of the graphene / polyvinyl alcohol / mineral polymer in the clayey cement rock-like material prepared according to the present invention;
[0043] Figure 7 The triaxial compression stress-strain curve of a similar material to clayey cementite without polyvinyl alcohol is shown in the figure. The peak strength, stress-strain curve change trend, strain softening characteristics, etc. are significantly different from those of the actual clayey cementite.
[0044] Figure 8 This is an electron microscope scanning image of a material similar to clayey impregnated cement rock without polyvinyl alcohol. It has poor cementation, loose structure, developed large pores, and no high molecular polymers. It is significantly different from the actual microstructural characteristics of clayey impregnated cement rock. DETAILED DESCRIPTION
[0045] The present invention will be further described below with reference to the accompanying drawings, specific embodiments and comparative examples.
[0046] Example 1
[0047] A clayey impermeable rock layer similar material in the embodiment includes the following components (by mass): 56.8 parts of quartz sand, 20.7 parts of kaolinite powder, 15.2 parts of montmorillonite powder, 0.1 parts of illite powder, 7.0 parts of plagioclase powder, 0.1 parts of potassium feldspar powder, 0.1 parts of dolomite powder, 0.02 parts of graphene, 11 parts of polyvinyl alcohol, and 22.2 parts of water. The purity of the mineral component materials quartz sand, kaolinite powder, montmorillonite powder, illite powder, plagioclase powder, potassium feldspar powder, and dolomite powder is 98%. Meanwhile, the quartz sand has a particle size of 1250 mesh; the kaolinite powder is calcined kaolinite powder with a particle size of 2500 mesh; the montmorillonite powder is natural montmorillonite powder with a particle size of 2000 mesh; the illite powder is natural illite powder with a particle size of 2500 mesh; the plagioclase powder is ultrafine plagioclase powder with a particle size of 2000 mesh; the potassium feldspar powder is natural potassium feldspar powder with a particle size of 2000 mesh; the dolomite powder is natural dolomite powder with a particle size of 2500 mesh; the graphene is powdered high-purity single-layer graphene with a particle size of 3 nm; the polyvinyl alcohol is PVA2488 cold water instant powdered polyvinyl alcohol with a viscosity of 55-68 mPa·s, and the water is deionized water.
[0048] The steps for preparing a similar material of a clayey impermeable rock layer in Example 1 are as follows:
[0049] S1: A typical clayey mudstone rock sample from a mining area in Northwest China was obtained through geological drilling. The diameter of the rock sample was 120 mm and the height of the rock sample was 150 mm.
[0050] S2: The triaxial compressive strength of the clayey impermeable rock layer mudstone obtained in step S1 was tested using the MTS815 electro-hydraulic servo rock mechanics experimental system and the SS-15 digital display mortar permeameter (stress-strain curves are shown in the attached manual). Figure 1 The triaxial compressive strength of the cement rock was determined to be 12.95 MPa and the permeability coefficient was 8.27×10 -6 m / d, and thus determine that the mass fraction of graphene is 0.02 parts and the mass fraction of polyvinyl alcohol is 11 parts;
[0051] S3: Use FEI Quanta 250 environmental scanning electron microscope and D8 Advance X-ray diffractometer to perform SEM scanning and XRD phase analysis on the mudstone sample obtained in step S1, and determine that the SEM scanning image and X-ray diffraction spectrum of the mudstone sample are as shown in the attached manual. Figure 2 , Attachment Figure 3 As shown, the particle size of the isolated cement rock sample is determined to be 10.4μm, and the types and contents of each mineral component are as follows:
[0052] Mineral component type Quartz sand Kaolinite powder Montmorillonite powder Illite Plagioclase Potassium feldspar dolomite Content (mass percentage) 56.8 20.7 15.2 0.1 7.0 0.1 0.1
[0053] S4: According to the actual particle size of the mudstone sample, the particle size of the quartz sand is determined to be 1250 mesh. At the same time, 56.8 parts of quartz sand, 20.7 parts of kaolinite powder, 15.2 parts of montmorillonite powder, 0.1 parts of illite powder, 7.0 parts of plagioclase powder, 0.1 parts of potassium feldspar powder, 0.1 parts of dolomite powder, 0.02 parts of graphene, and 11 parts of polyvinyl alcohol are weighed and mixed evenly by a dry powder mixer;
[0054] S5: weigh 22.2 parts of deionized water;
[0055] S6: Add the deionized water weighed in step S5 to the mixed dry materials obtained in step S4, and stir quickly and evenly to obtain a clayey cement rock-like material.
[0056] The clayey cement rock-like material prepared above was pressed into shape to make standard mechanical test specimens and permeability test specimens with a diameter of 50 mm and a height of 100 mm, and the specimens were placed in a constant temperature and humidity curing box for 7 days. On this basis, triaxial compressive strength, permeability and microstructure tests of similar materials were carried out.
[0057] Comparative Example 1 (without polyvinyl alcohol)
[0058] A similar material of clayey impermeable rock layer in Comparative Example 1 includes the following components (by mass): 56.8 parts of quartz sand, 20.7 parts of kaolinite powder, 15.2 parts of montmorillonite powder, 0.1 parts of illite powder, 7.0 parts of plagioclase powder, 0.1 parts of potassium feldspar powder, and 0.1 parts of dolomite powder. The purity of illite powder, plagioclase powder, potassium feldspar powder, and dolomite powder is 98%. 0.02 parts of graphene, 0 parts of polyvinyl alcohol, and 22.2 parts of water. The purity of the mineral component materials quartz sand, kaolinite powder, montmorillonite powder, illite powder, plagioclase powder, potassium feldspar powder, and dolomite powder is 98%. At the same time, the quartz sand particle size is 1250 mesh; the kaolinite powder is calcined kaolinite powder, and the particle size is 2500 mesh; the montmorillonite powder is natural montmorillonite powder, and the particle size is 2000 mesh; the illite powder is natural illite powder, and the particle size is 2500 mesh; the plagioclase powder is ultrafine plagioclase powder, and the particle size is 2000 mesh; the potassium feldspar powder is natural potassium feldspar powder, and the particle size is 2000 mesh; the dolomite powder is natural dolomite powder, and the particle size is 2500 mesh; the graphene is powdered high-purity single-layer graphene, and the particle size is 3nm; the water is deionized water. The preparation steps of a similar material of a clay impermeable rock layer in Comparative Example 1 are as follows:
[0059] S1: A typical clayey mudstone rock sample from a mining area in Northwest China was obtained through geological drilling. The diameter of the rock sample was 120 mm and the height of the rock sample was 150 mm.
[0060] S2: The triaxial compressive strength of the clayey impermeable rock layer mudstone obtained in step S1 was tested using the MTS815 electro-hydraulic servo rock mechanics experimental system and the SS-15 digital display mortar permeameter (stress-strain curves are shown in the attached manual). Figure 1 The triaxial compressive strength of the cement rock was determined to be 12.95 MPa and the permeability coefficient was 8.27×10 -6 m / d, and thus determine the mass fraction of graphene to be 0.02 parts;
[0061] S3: Use FEI Quanta 250 environmental scanning electron microscope and D8 Advance X-ray diffractometer to perform SEM scanning and XRD phase analysis on the mudstone sample obtained in step S1, and determine that the SEM scanning image and X-ray diffraction spectrum of the mudstone sample are as shown in the attached manual. Figure 2 , Attachment Figure 3 As shown, the particle size of the isolated cement rock sample is determined to be 10.4μm, and the types and contents of each mineral component are as follows:
[0062] Mineral component type Quartz sand Kaolinite powder Montmorillonite powder Illite Plagioclase Potassium feldspar dolomite Content (mass percentage) 56.8 20.7 15.2 0.1 7.0 0.1 0.1
[0063] S4: According to the actual particle size of the mudstone sample, the particle size of the quartz sand is determined to be 1250 mesh. At the same time, 56.8 parts of quartz sand, 20.7 parts of kaolinite powder, 15.2 parts of montmorillonite powder, 0.1 parts of illite powder, 7.0 parts of plagioclase powder, 0.1 parts of potassium feldspar powder, 0.1 parts of dolomite powder, and 0.02 parts of graphene are weighed and mixed evenly with a dry powder mixer;
[0064] S5: weigh 22.2 parts of deionized water;
[0065] S6: Add the deionized water weighed in step S5 to the mixed dry materials obtained in step S4, and stir quickly and evenly to obtain a clayey cement rock-like material.
[0066] The clayey cement rock-like material prepared above was pressed into shape to make standard mechanical test specimens and permeability test specimens with a diameter of 50 mm and a height of 100 mm, and the specimens were placed in a constant temperature and humidity curing box for 7 days. On this basis, triaxial compressive strength, permeability and microstructure tests of similar materials were carried out.
[0067] The stress-strain curve of the triaxial compression process of the similar material in Example 1 is shown in the attached manual. Figure 4 Compare the actual stress-strain curve of clayey impermeable rock layer triaxial compression (see Appendix Figure 1) It can be seen that the stress-strain curve change trend, strain softening and plastic deformation characteristics of similar materials and natural rock mass are basically consistent. At the same time, the triaxial compressive strength of the similar material is 0.074MPa. According to the stress similarity ratio of 1:167, the strength of the mudstone rock mass simulated by the similar material is 12.38MPa, and the relative error with the real mudstone rock mass strength is only 4.4%, and the strength similarity is good.
[0068] The test results show that the permeability coefficient of the similar material in Example 1 is 7.81×10 -7 m / d. According to the permeability similarity ratio of 1:10, the permeability of mudstone simulated by similar materials is 7.81×10 -6 m / d, and the relative error with the real mudstone permeability coefficient is 5.6%, and the permeability similarity is good.
[0069] The electron microscope scanning images of similar materials in Example 1 were obtained by testing as shown in the attached manual. Figure 5 Comparative analysis is shown in Appendix Figure 2 , Attachment Figure 5 , by the attached Figure 2 It can be seen that the natural barrier cement rock has a dense structure and low porosity. Figure 5 It can be seen that the similar material is rich in polymers, has good overall cementation, and a dense structure. Its microstructural characteristics are similar to those of actual clayey impermeable cementite. This is because the polyvinyl alcohol organic polymer compound has an irregular linear structure composed of many chain links, which undergoes polymerization reactions with graphene and mineral component materials in the similar material to generate graphene / polyvinyl alcohol / mineral polymers, making the overall cementation of the similar material better, and the permeability and microstructural characteristics are more similar to those of actual natural clayey impermeable cementite. Among them, the graphene / polyvinyl alcohol / mineral polymer is expressed in the following forms: Figure 6 As shown, the polymerization reaction equation is:
[0070] C(n)(graphene)+[C2H4O] n (polyvinyl alcohol) + Ms (mineral) = C (n) / [C2H4O] n / Ms(polymer)
[0071] The stress-strain curve of the similar material in the comparative example 1 during the triaxial compression process is shown in the attached manual. Figure 7 Compare the actual stress-strain curve of clayey impermeable rock layer triaxial compression (see Appendix Figure 1) shows that the similar material has poor consistency with the natural rock mass stress-strain curve change trend, strain softening and plastic deformation characteristics. At the same time, the triaxial compressive strength of the similar material is only 0.046MPa. According to the stress similarity ratio of 1:167, the strength of the mudstone simulated by the similar material is 7.68MPa, which is much smaller than the 12.95MPa of the real mudstone. The relative error with the real mudstone strength is only 40.7%, and the strength similarity is obviously insufficient.
[0072] The test results show that the permeability coefficient of the similar material in Comparative Example 1 is 1.28×10 -6 m / d. According to the permeability similarity ratio of 1:10, the permeability of mudstone simulated by similar materials is 1.28×10 -5 m / d, which is much larger than the 8.27×10 -6 m / d, and the relative error of the permeability coefficient of the real mudstone is 54.8%, and the permeability similarity is extremely different.
[0073] The electron microscope scanning images of similar materials in Comparative Example 1 are obtained by testing as shown in the attached manual. Figure 8 Compared with similar materials in Example 1 (see Figure 5 ), attached Figure 8 Similar materials in the literature have poor cementation, loose structure, developed macropores, and no polymers. Their microstructural characteristics are very different from those of actual natural clayey cementite (see Appendix Figure 2 ). This shows that when polyvinyl alcohol is not present, the graphene and mineral component materials in similar materials are difficult to undergo polymerization reactions and cannot generate high molecular polymers. The strength, permeability, and microstructural characteristics of similar materials are significantly different from those of actual natural clay-based cement rock.
Claims
1. A clayey impermeable rock layer similar material, characterized in that: It includes mineral component materials, strength adjustment materials, permeability adjustment and cementing materials and water, wherein the mineral component materials include 10-90 parts of quartz sand, 5-70 parts of kaolin powder, 5-50 parts of montmorillonite powder, 0.1-30 parts of illite powder, 0.1-30 parts of plagioclase powder, 0.1-20 parts of potassium feldspar powder, and 0.1-20 parts of dolomite powder. The strength adjustment material is 0.01-0.05 parts of graphene, the permeability adjustment and cementing material is 5-15 parts of polyvinyl alcohol, and the water is deionized water accounting for 15-25% of the total weight of the total material; the above components are all calculated by mass. The sum of the mass fractions of each component in the mineral component material is 100 parts, and the content fraction of each component is determined according to the actual content ratio of each component in the natural clayey impermeable rock mass; The mass fractions of the graphene and polyvinyl alcohol are determined according to the triaxial compressive strength and permeability coefficient of the natural rock mass of the clayey impermeable rock layer, respectively. The detailed determination scheme is shown in the following table: 。 2. The clayey impermeable rock layer similar material according to claim 1, characterized in that: The mineral component materials are high-purity mineral materials, with the purity of each component being ≥ 98%; The quartz sand particle size is 100-2000 mesh, and the selection of the particle size is determined according to the actual particle size of the clayey water-proof natural rock mass; The kaolinite powder is calcined kaolinite powder, and the particle size is 2500-3000 mesh; The montmorillonite powder is natural montmorillonite powder, and the particle size is 2000-3000 mesh; The illite powder is natural illite powder with a particle size of 2500-3000 mesh; The plagioclase powder is ultrafine plagioclase powder with a particle size of 2000-3000 mesh; The potassium feldspar powder is natural potassium feldspar powder, and the particle size is 2000-3000 mesh; The dolomite powder is natural dolomite powder, and the particle size is 2500-3000 mesh.
3. The clayey water-insulating rock layer similar material according to claim 1, characterized in that: The graphene is powdered high-purity single-layer graphene with a particle size of 3-9nm.
4. The clayey impermeable rock layer similar material according to claim 1, characterized in that: The polyvinyl alcohol is PVA2488 cold water instant powdered polyvinyl alcohol with a viscosity of 55-68 mPa·s.
5. The clayey water-insulating rock layer similar material according to claim 1, characterized in that: This similar material is suitable for physical similarity simulation experiments with a geometric similarity ratio of 1:100, a stress similarity ratio of 1:167, a time similarity ratio of 1:10, and a permeability coefficient similarity ratio of 1:
10.
6. The method for preparing a clayey impermeable rock layer similar material as claimed in claim 1, characterized in that: The following steps are involved: S1: Obtain natural rock samples of clayey impermeable rock strata through geological drilling; where: the diameter of the rock sample is ≥100mm, and the height of the rock sample is ≥120mm; S2: Perform triaxial compressive strength and permeability test on the natural rock sample of the clayey impermeable rock layer obtained in step S1 to determine the triaxial compressive strength and permeability of the impermeable rock sample; S3: Obtain a natural rock sample of a clayey impermeable rock layer according to step S1, and determine the particle size, type and content of each mineral component of the impermeable rock sample; S4: according to the particle size of the water-blocking rock sample, the triaxial compressive strength, the permeability coefficient, the type and content of each mineral component obtained in steps S2 and S3, the particle size of the quartz sand particles is determined, and the mass fractions of quartz sand, kaolinite powder, montmorillonite powder, illite powder, plagioclase powder, potassium feldspar powder, dolomite powder, graphene and polyvinyl alcohol are weighed, and the above materials are uniformly stirred by a dry powder mixer to obtain a dry material mixture; S5: According to the mass fraction of the dry material mixture obtained in step S4, deionized water of 15-25% of the mass fraction of the dry material mixture is weighed, added to the dry material mixture obtained in step S4, and quickly stirred to obtain the desired similar material.
7. A method for preparing a clayey water-insulating rock layer similar material as claimed in claim 6, characterized in that: In step S3, the natural rock sample of the clayey impermeable rock layer obtained in step S1 is subjected to SEM scanning and XRD phase analysis to finally determine the particle size of the impermeable rock sample and the type and content of each mineral component.
Citation Information
Patent Citations
Fluid-solid coupled similar material by taking polyurethane as cementing agent and preparation method thereof
CN107098655A
Fluid-solid coupling similar material and preparation method thereof
CN112028555A
Preparation method of artificial shale rock cores based on inorganic glue ratio
CN108426753A
Preparation method of tight sandstone oil displacement rock core with argillaceous interlayer
CN113532990A
Low-permeability dispersion-resistant rock permeation modified material
CN114436585A